Publisher Correction: The β20–β21 of gp120 is a regulatory switch for HIV-1 Env conformational transitions - Alon Herschhorn (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author Amos B. Smith, III, which was incorrectly given as Amos B. SmithIII. This has now been corrected in both the PDF and HTML versions of the Article.